2008
DOI: 10.2514/1.37869
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Operation of Pulse-Detonation Engine-Driven Ejectors

Abstract: Experimental studies were performed to improve the understanding of the operation of ejector augmenters driven by a pulse-detonation engine. The research employs an H 2 -air pulse-detonation engine at an operating frequency of 30 Hz. Static pressure was measured along the interior surface of the ejector, including the inlet and exhaust sections. Thrust augmentation provided by the ejector was calculated by integration of the static pressure measured along the ejector geometry. The computed thrust augmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…From this test desired results are achieved in tapered ejector configuration. Glaser et al [56] conducted an experiment on the operation of pulse detonation engine-driven ejectors. The experimental studies employed an H 2 -air mixture in PDE with ejectors to improve the performance augmenters driven.…”
Section: Reviews On Experimental Analysismentioning
confidence: 99%
“…From this test desired results are achieved in tapered ejector configuration. Glaser et al [56] conducted an experiment on the operation of pulse detonation engine-driven ejectors. The experimental studies employed an H 2 -air mixture in PDE with ejectors to improve the performance augmenters driven.…”
Section: Reviews On Experimental Analysismentioning
confidence: 99%
“…The experimental studies were employed an H2-air pulse detonation engine to improve the operation of ejector augmenters driven. In this research, straight and diverging ejectors were investigated (Glaser, A. J. et al, 2008 The simulated results show that exergy loss in the deflagration combustion process is higher in comparison to the detonation combustion process. Higher efficiency of exergy was also observed in lesser fuel mass fraction.…”
Section: Fig 1 Mass Flow Through the Ejector (Zheng F Et Al 2011)mentioning
confidence: 99%
“…It should be noticed that the maximum thrust augmentation was still located at the upstream of the detonation exit in the whole range of the ejector axial position tested by Wilson et al Furthermore, previous experiments indicated that many operating parameters such as the PDE cycle frequency 10,15 and fill fraction 11 affect the PDEejector performance as well. However, the focuses in these previous investigations [10][11][12][13][14][15][16] were thrust augmentation not acoustic performance. It is expected that the noise radiation performances of PDE by the addition of an ejector will have the similar change trend to ones of thrust augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it seemed useful to investigate this phenomenon. Some researchers [11][12][13] have found a maximum thrust augmentation with ejector being downstream of the detonation tube exit, other with it upstream.…”
Section: Introductionmentioning
confidence: 99%